2021
DOI: 10.1038/s41598-020-80169-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute systemic loss of Mad2 leads to intestinal atrophy in adult mice

Abstract: Chromosomal instability (CIN) is a hallmark of cancer, leading to aneuploid cells. To study the role that CIN plays in tumor evolution, several mouse models have been engineered over the last 2 decades. These models have unequivocally shown that systemic high-grade CIN is embryonic lethal. We and others have previously shown that embryonic lethality can be circumvented by provoking CIN in a tissue-specific fashion. In this study, we provoke systemic high-grade CIN in adult mice as an alternative to circumvent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…Consistently, gastrointestinal stem cells and the transient amplifying pool seemed to be the most affected cells by MAD2 overexpression and extended mitosis as an imbalance in MAD2 expression in either direction can cause prolonged SAC activation 27, 29 . Our finding is well in line with a recent report showing that timed conditional deletion of MAD2 in Mad2l1 f/f mice carrying a CRE ERT2 transgene triggers a similar phenotype with rapid weight loss, mitotic abnormalities and increased apoptosis in intestinal crypts, causing rapid animal death 63 .…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, gastrointestinal stem cells and the transient amplifying pool seemed to be the most affected cells by MAD2 overexpression and extended mitosis as an imbalance in MAD2 expression in either direction can cause prolonged SAC activation 27, 29 . Our finding is well in line with a recent report showing that timed conditional deletion of MAD2 in Mad2l1 f/f mice carrying a CRE ERT2 transgene triggers a similar phenotype with rapid weight loss, mitotic abnormalities and increased apoptosis in intestinal crypts, causing rapid animal death 63 .…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, gastrointestinal stem cells and the transient amplifying pool seemed to be the most affected cells by MAD2 overexpression and extended mitosis as an imbalance in MAD2 expression in either direction can cause prolonged SAC activation (Michel et al, 2001 ; Sotillo et al, 2007 ). Our finding is well in line with a recent report showing that timed conditional deletion of MAD2 in Mad2l1 f/f mice carrying a CRE ERT2 transgene triggers a similar phenotype with rapid weight loss, mitotic abnormalities and increased apoptosis in intestinal crypts, causing rapid animal death (Schukken et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Mouse models have shown that impairing the SAC promotes chromosome mis‐segregation and tumor formation (Baker et al , 2005 ; Holland & Cleveland, 2009 ; Schvartzman et al , 2010 ). Completely abolishing the SAC, however, is detrimental to human cells (Dobles et al , 2000 ; Kops et al , 2004 ; Michel et al , 2004 ; Schukken et al , 2021 ), and suppression of the SAC may in fact be a successful therapeutic strategy against some cancer types (Cohen‐Sharir et al , 2021 ; Quinton et al , 2021 ). Together, these results indicate that tuning SAC function can make the difference between normal growth, cancerous growth, and cell death.…”
Section: Introductionmentioning
confidence: 99%